Strategi Pengembangan Produk Sehat Dalam Bisnis Wirausaha Makanan: Pendekatan Inovatif Untuk Meningkatkan Status Gizi Masyarakat - Marifat Istiqa Mukty; Dita Pulubuhu (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
public health is an important issue that requires serious attention from business people, especially in the food sector. This study aims to explore healthy product development strategies in the context of food entrepreneur business as an innovative approach to improve people's nutritional status. Through a qualitative approach with case studies of several successful food entrepreneurs, this study analyzes the strategies used in the development of healthy products and their implications for improving the nutritional status of the community. The results showed that the selection of high-quality raw materials, the use of modern production technology, creative promotion, and cooperation with related parties are some of the effective strategies in the development of healthy products in the food entrepreneurial business.